Leadership, teamwork and work outcomes in healthcare: A test of a model - Elaine R. Neiva; Ricardo S. S. Durães; Gardênia da Silva Abbad; Andreas Xyrichis (PLoS ONE, 2026)
Effective teamwork in healthcare improves patient outcomes, staff well-being, and service delivery. To enhance these benefits, NHS teams should implement targeted leadership training, routinely assess and clarify roles to reduce ambiguity, and encourage staff participation in decision-making to boost autonomy. Researchers analysed 2022 and 2023 NHS Staff Survey data using Structural Equation Modelling. Main findings: (1) Effective leadership boosts teamwork and, in turn, engagement and well-being; (2) Teamwork can raise role ambiguity and lessen autonomy, leading to stress; (3) Leadership is key to managing these issues. Thus, boosting autonomy and reducing ambiguity support better team performance and staff well-being. The study highlights the need for leadership programmes to strengthen team dynamics and reduce uncertainty.